The Oxford encyclopedia of the modern Islamic world - THE_OXFORD (Oxford University Press, 1995)
ir, Jil.1,c.1-6 ; Jil.2,c.1-6 ; Jil.3,c.1-6 ; Jil.4,c.1-6/ stoc3, jl.1, c. 1-6, jl.2, c. 1-6, jl.3, c. 1-6, jl.4, c. 1-6